2006
DOI: 10.1590/s0100-879x2006000800009
|View full text |Cite
|
Sign up to set email alerts
|

Urinary NO3 excretion and renal failure in indinavir-treated patients

Abstract: Treatment with indinavir (IDV), a protease inhibitor, is frequently associated with renal abnormalities. We determined the incidence of renal failure (creatinine clearance <80 mL min -1 1.73 (m 2 ) -1 ) in HIV patients treated with highly active antiretroviral therapy, including IDV, and investigated the possible mechanisms and risk factors of IDV nephrotoxicity. Thirty-six patients receiving IDV were followed for 3 years. All were assessed for age, body weight, duration of infection, duration of IDV treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…HIV patients treated with Indinavir presented lower urinary excretion of the NO metabolite NO 3 [82]. Wang et al demonstrated that Indinavir, at a clinical plasma concentration, can cause endothelial dysfunction through eNOS (endothelial nitric oxide synthase) down-regulation in porcine pulmonary artery rings and HPAECs (human pulmonary arterial endothelial cells), and that endothelium-dependent relaxation of the vessel rings was also reduced following Indinavir treatment [83].…”
Section: Discussionmentioning
confidence: 99%
“…HIV patients treated with Indinavir presented lower urinary excretion of the NO metabolite NO 3 [82]. Wang et al demonstrated that Indinavir, at a clinical plasma concentration, can cause endothelial dysfunction through eNOS (endothelial nitric oxide synthase) down-regulation in porcine pulmonary artery rings and HPAECs (human pulmonary arterial endothelial cells), and that endothelium-dependent relaxation of the vessel rings was also reduced following Indinavir treatment [83].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies conducted by our group in patients and in animal models, we found that indinavir also decreases NO production. 28,29…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with indinavir has been found to be frequently associated with renal abnormalities and causes renal failure. 43 Lipodystrophy and other fat distribution disorders have been reported in patients receiving PI therapy for HIV infection. 44 PIs are reported to cause hepatotoxicity at any time from the start of medication.…”
Section: Viral Protease Inhibitors and Toxicity Of Antiprotease Drugsmentioning
confidence: 99%